The problem of illegal immigration on international relations is a study in light of Libyan-Italian relations to reduce her problems (Journal of Human Sciences, 2021)
The study aimed to find out the problem of illegal immigration on international relations in that it represents an obsession threatening international relations between countries that represent a source of immigrants, as well as countries that receive them, and countries of transit and therefore we wanted to discuss the problem of illegal immigration on Libyan-Italian relations. The frequency of the number of illegal immigrants through Libya towards Italy, the more cooperation between the two countries in concluding bilateral agreements strengthens the relationship between the two parties, and this is in addition to the increase in the frequency between the two countries. How to address this worsening phenomenon, which in turn is a cause of tension in political, diplomatic and economic relations between the exporting countries and the transit countries and countries.